Studi Victimologis terhadap Korban Kejahatan Siber pada Anak dan Implikasinya terhadap Perlindungan Hukum - Risma Amelia; Hana Faridah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study analyzes criminal legal protection for adolescents as victims of cybercrime in Indonesia and formulates an ideal protection concept based on victimology and the best interest of the child principle. Using a normative juridical method with statutory and conceptual approaches, the findings show that Indonesian regulation remains fragmentary and repressive toward offenders, failing to comprehensively protect adolescent victims. The proposed ideal concept integrates repressive, preventive, and restorative protection within a layered model involving family, school, state, and society. The research affirms the urgency of reconstructing criminal law that is responsive and just for adolescents in the digital era.